Kontribusi Dukungan Sosial terhadap Penerimaan Diri pada Orang dengan HIV/AIDS - Lambutu, Nadia; Komarudin Komarudin; Agus Salim (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study focuses on the relationship between social support and self-acceptance levels in individuals living with HIV/AIDS (PLWHA). This study was conducted using a quantitative approach with a correlational design, involving 60 PLWHA respondents from a foundation in Yogyakarta, selected through purposive sampling. Data collection used the self-acceptance scale instrument by Bernard (2019) and the social support scale developed by Zimet and colleagues (2021). Statistical testing results showed a significant positive correlation between the two variables (r = 0.528), where social support contributed 36.2% to the variation in self-acceptance. This finding suggests that support from the immediate environment plays a crucial role in helping PLWHA achieve better self-acceptance. This study highlights that social support, including emotional and practical assistance, contributes significantly to the psychological well-being of PLWHA. Furthermore, these findings underscore the need for professional and family support systems in fostering self-acceptance among individuals facing the challenges of HIV/AIDS. This study provides valuable insights into psychosocial interventions that can improve the quality of life of PLWHA, emphasizing the crucial role of social networks in the acceptance process.